Cystine and Theanine supplementation restores high-intensity resistance exercise-induced attenuation of natural killer cell activity in well-trained men - Kawada, S.; Kobayashi, K.; Ohtani, M.; Fukusaki, C. (The Journal of Strength and Conditioning Research, 2010)
We investigated the effects of supplementation with cystine, a dipeptide of cysteine, and theanine (CT), a precursor of glutamate, on immune variables during high-intensity resistance exercise. Cysteine and glutamate are involved in the formation of glutathione, which modulates the activity of natural killer (NK) cells. In this double-blinded clinical trial, 15 well-trained men (aged 22.8 ± 4.0 years) were divided into 2 groups: placebo (n = 7) and CT (n = 8). The placebo group was administered a powder containing cellulose (950 mg) and glutamate (30 mg), whereas the CT group was administered a powder containing cystine (700 mg) and theanine (280 mg), once daily for 2 weeks. The subjects trained according to their normal schedule (3 times per week) in the first week and trained at double the frequency (6 times per week) in the second week. Concentrations of immunoglobulin (Ig)M, interleukin (IL)-6, IL-8, and salivary IgA and the leukocyte count did not change significantly in either group. There was a significant decrease (p = 0.05) in the NK cell activity (NKCA) in the placebo group after the second week compared with that in the CT group (placebo: 69.2 ± 16.1% vs. CT: 101.7 ± 38.7%). Phytohemagglutinin-induced lymphocyte blastoid transformation did not change significantly in either group. These results suggest that NKCA is not affected in a normal training schedule with or without CT supplementation. However, high-intensity and high-frequency resistance exercises cause attenuation of NKCA, which CT supplementation appears to restore. Therefore, in practical application, CT supplementation would be useful for athletes to restore the attenuation of NKCA during high-intensity and high-frequency training.